EDUKASI PENGUATAN NILAI PENTING CAGAR BUDAYA KEPADA GURU DAN SISWA UNTUK PELESTARIAN BERKELANJUTAN - Rachmadyanti, Resza; Nini A. Kiay Demak; Ari Putra Rachman (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Gorontalo City is an area wich with numerous relics from the colonial period. As a witness to the city’s long history, it possesses many cultural heritage assets, including heritage objects, cultural structures, and heritage buildings. This community service project aims to cultivate a sense of awareness, ownership, and an understanding of the significant value of this cultural heritage. To achieve this, educational effort focused on introducing the cultural heritage site in the Old Town area of Gorontalo are essential, particulary targeting the younger generation. The partners in this activity were the students and teachers of State Senior High School (SMA Negeri) 3 Gorontalo. The program was carried out in several stages: observation, material preparation, and the implementation of socialization sessions. Through this community service program, it is expected to foster awareness and concern among the youth of Gorontalo to safeguard and preserve their historical legacy and cultural identity.